2000
DOI: 10.1046/j.0019-2805.2000.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of chemokine production at the blood–retina barrier

Abstract: SUMMARYChemokine production at the blood±retina barrier probably plays a critical role in determining the in¯ux of tissue-damaging cells from the circulation into the retina during in¯ammation. The blood± retina barrier comprises the retinal microvascular endothelium and the retinal pigment epithelium. Chemokine expression and production by human retinal microvascular endothelial cells (REC) have never been reported previously, so we examined the in vitro expression and production of monocyte chemoattractant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 39 publications
(52 reference statements)
4
43
0
1
Order By: Relevance
“…The cytokines and mediators are said to contribute actively to DR-associated damage to the retinal vasculature and neovascularization. 23 RANTES produced by inflammatory cells, retinal endothelial cells, and pigment epithelial cells 24 is a member of the chemokine family. Meleth et al 7 showed that RANTES levels largely increased in subjects with severe NPDR versus less severe NPDR (Po0.001), but RANTES levels unexpectedly decreased in subjects with less severe NPDR versus normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines and mediators are said to contribute actively to DR-associated damage to the retinal vasculature and neovascularization. 23 RANTES produced by inflammatory cells, retinal endothelial cells, and pigment epithelial cells 24 is a member of the chemokine family. Meleth et al 7 showed that RANTES levels largely increased in subjects with severe NPDR versus less severe NPDR (Po0.001), but RANTES levels unexpectedly decreased in subjects with less severe NPDR versus normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…These findings implicate a possible mechanism underlying the observed protective effect of this allele. RPE cells constitutively express CCL2, a CC chemokine, and secrete VEGF, a growth factor and cytokine [Holtkamp et al, 1999;Crane et al, 2000]. Increased levels of both CCL2 and VEGF in RPE cells are related to oxidative stress and hypoxia within the eye [Spilsbury et al, 2000;Uetama et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro expression and production of IL-8 and MCP-1 by human retinal endothelial cells and HRPE after stimulation by pro-inflammatory cytokines have been reported. 10 MCP-1 significantly reduced ZO-1 protein expression in a mouse model of experimental autoimmune uveoretinitis. 24 Recently, Funk et al 25 reported elevated aqueous humour levels of IL-8 and MCP-1 in patients with CRVO, but not in those with BRVO.…”
Section: Il-8 and Mcp-1 In Brvo Macular Oedemamentioning
confidence: 91%
“…[7][8][9] Moreover, both IL-8 and MCP-1 are expressed by human retinal endothelial cells and retinal pigment epithelial cells (HRPE). 10 In this study, we measured the concentrations of IL-8 and MCP-1 in vitreous fluid of patients with macular oedema secondary to BRVO to investigate the relationship between the development of macular oedema and the vitreous levels of these chemokines.…”
Section: Introductionmentioning
confidence: 99%